Media sosial sebagai pembentuk opini publik di kalangan generasi z - Maulana, Muhammad Dimas (Maliki Interdisciplinary Journal, 2025)
This study examines the role of social media in shaping public opinion among Generation Z (born ±1997-2012) in Indonesia. In today’s digital era, Generation Z, who grew up as digital natives, has experienced a significant transformation in how they access information and form perspectives on various issues. This study analyzes the characteristics of Generation Z’s digital media consumption, identifies the most influential platforms, and explores the mechanisms of opinion formation through digital interactions. Using qualitative and quantitative analysis approaches, the study found that TikTok and Instagram are the dominant platforms with significant influence, while the echo chamber and filter bubble phenomena strengthen opinion polarization. The findings show that Generation Z is not just a passive consumer of information, but also an active producer of opinion through the content they create. The case study of the “#IndonesiaBergerak Movement” illustrates how social media mobilizes collective opinion into a real movement that influences public policy. This study recommends strengthening digital literacy, further cross-platform studies, and regulations that encourage algorithm transparency to create a healthier and more constructive digital ecosystem for public opinion formation.